STRUCTURAL, MORPHOLOGICAL AND DISSOLUTION PROPERTIES OF ZrO₂-BASED BIOCOMPOSITES FOR DENTAL APPLICATIONS - BIZO, Liliana; SABO, Klara; BARÁBAS, Réka; KATONA, Gabriel; BARBU-TUDORAN, Lucian; BERAR, Antonela (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In the present work, zirconia-based biocomposites were prepared by adding different amounts of antibacterial magnesium oxide and bioactive and biocompatible hydroxyapatite (HAP). The biocomposites were synthesized by the conventional ceramic processing route. The structure and morphology of the materials were investigated using X-ray powder diffraction (XRPD), scanning and transmission electronic microscopy (SEM and TEM). The stability of the tetragonal structure of ZrO₂ was confirmed by XRPD analyses. Moreover, their bioactivity was studied by soaking the samples in artificial saliva (AS) to evaluate the effect of MgO and HAP on the biological performances of the prepared biocomposites. UV-VIS analyses carried out on artificial saliva after immersion of the prepared materials showed that MgO plays an important role in the post-immersion dissolution process.